(untitled) (INNOVATIVE ECONOMY, 2020)
Fedoryshyna L.M. RESEARCH OF THE CURRENT STATE OF HEALTH OF THE CHILDREN’S POPULATION OF UKRAINE Purpose. The purpose of the study is to research on the basis of statistical data on the current state of health of the children’s population of Ukraine and the identification of regional differences on this basis. Methodology of research. The theoretical basis of the research is the scientific work of domestic scientists on the problem under study, and the information base ‑ data of the State Statistics Service of Ukraine. In the process of work were used general scientific methods and techniques: formal logic, statistical analysis ‑ to study the health status of the children’s population of Ukraine and its incidence by class of diseases in a regional section; tabular ‑ for visual representation of statistical information and results obtained; abstract-logical ‑ in substantiating the theoretical positions and formulating conclusions. Findings. On the basis of state statistical information, an analysis of the health status of the children’s population of Ukraine was carried out. The grouping of regions of Ukraine according to the number of the first registered cases of diseases by classes of diseases of children aged 0-17 years in 2016 has been carried out. It was established that the largest proportion of the diseases was recorded in Dnipropetrovsk, Lviv regions and Kyiv, and the smallest in the Luhansk, Sumy, Chernivtsi and Kherson regions; the most common diseases for almost all regions are respiratory diseases and diseases of the skin and subcutaneous tissue. Originality. Based on a thorough study of official statistical information on the health status of the children’s population of Ukraine in the regional section, results have been obtained that may serve as the basis for the development of certain regional programs for the protection of child health. Practical value. The obtained results can be used to develop an effective concept for the formation and preservation of the health of the child population as the basis for the health and safety of the Ukrainian people, its reproductive, intellectual and labour potential. Key words: child population; health; morbidity; region; diseases.